UNETHICAL LEADERSHIP AND FOLLOWERS' DEVIANCE: THE MEDIATING ROLE OF PERCEPTION OF POLITICS AND INJUSTICE (Singaporean Journal of Business Economics and Management, 2019)
This paper argued that unethical leadership behavior increases followers' deviance by increasing perception of injustice and politics in organizations. More specifically, perception of politics and injustice mediates the relationship between unethical leadership behavior and followers' deviance. By using data from 262 employees of the public organizations in Ethiopia, we confirmed our hypothesis. Further, the result of multiple regression confirmed that the relationship between unethical leadership behavior and followers deviance would be stronger when followers develop a perception of politics in the workplace.